2016
DOI: 10.1007/s00787-016-0918-2
|View full text |Cite
|
Sign up to set email alerts
|

Latent classes of emotional and behavioural problems in epidemiological and referred samples and their relations to DSM-IV diagnoses

Abstract: Researchers’ interest have recently moved toward the identification of recurrent psychopathological profiles characterized by concurrent elevations on different behavioural and emotional traits. This new strategy turned to be useful in terms of diagnosis and outcome prediction. We used a person-centred statistical approach to examine whether different groups could be identified in a referred sample and in a general-population sample of children and adolescents, and we investigated their relation to DSM-IV diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 39 publications
(49 reference statements)
4
33
0
Order By: Relevance
“…The significance level was set at p < 0.05 and effect size was expressed as Cohen's d or Wilcoxon's r, as required. We aimed to control these analyses for possible confounding variables such as medication (The MTA Cooperative Group, 1999), social economic status (Nobile et al 2010, Biederman et al 2002 and comorbidity (Frigerio et al 2006, Bianchi et al 2017, which were found to be associated with severity of symptoms and different response to treatment. Gender and age were not included in our list of covariates, because we analysed CPRS T-scores, which are already weighed for age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…The significance level was set at p < 0.05 and effect size was expressed as Cohen's d or Wilcoxon's r, as required. We aimed to control these analyses for possible confounding variables such as medication (The MTA Cooperative Group, 1999), social economic status (Nobile et al 2010, Biederman et al 2002 and comorbidity (Frigerio et al 2006, Bianchi et al 2017, which were found to be associated with severity of symptoms and different response to treatment. Gender and age were not included in our list of covariates, because we analysed CPRS T-scores, which are already weighed for age and gender.…”
Section: Discussionmentioning
confidence: 99%
“…Within this theoretical framework, early RPs are viewed as the starting point of a trajectory of self‐regulatory problems (Winsper & Wolke, ), which may manifest as daytime co‐occurring internalising and externalising behaviour problems (Williams, Berthelsen, Walker, Nicholson, ). These problems, in turn, can increase the risk of a range of psychopathological outcomes including personality disorders (Halperin, Rucklidge, Powers, Miller, & Newcorn, ), DSM‐IV diagnoses (mood, anxiety, ADHD) and comorbidity (Bianchi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the majority of children stayed in the ‘Low’ group from ages 6/7–10/11 years is consistent with other research (Luby et al ., 2003; Althoff et al ., 2006, 2010 b ; Basten et al ., 2013, Bonadio et al ., 2016; Weeks et al ., 2016; Bianchi et al ., 2017). The largest proportion of individuals who were in the ‘Moderate’ or the ‘Hyperactivity/internalizing’ profiles at age 6/7 years also ended up in the ‘Low’ profile by age 10/11 years.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, constructs of co-occurring internalizing/externalizing, such as the Child Behavior Checklist (CBCL) Dysregulation profile have also been identified (Biederman et al ., 1995). This is a widely replicated profile of problem behavior in which children score high on symptoms of emotional and behavioral self-regulation (De Caluwé et al ., 2013; Masi et al ., 2015; Bianchi et al ., 2017). Beyond the types of symptoms exhibited, there has also been variation in severity, where mild, moderate, and severe levels of internalizing, externalizing, and co-occurrence between the two has been observed, supporting nuance beyond diagnostic thresholds (DiStefano and Kamphaus, 2006; Ostrander et al ., 2008; Mindrila, 2016).…”
Section: Introductionmentioning
confidence: 99%